Authenticity and Corporate Governance - Steckler, Erica (Journal of business ethics, 2019)
Although personal attributes have gained recognition as an important area of effective corporate governance, scholarship has largely overlooked the value and implications of individual virtue in governance practice. We explore how authenticity—a personal and morally significant virtue—affects the primary monitoring and strategy functions of the board of directors as well as core processes concerning director selection, cultivation, and enactment by the board. While the predominant focus in corporate governance research has been on structural factors that influence firm financial outcomes, this paper shifts attention to the role of authenticity and its relationship to individual board member qualities and collective board activities. We explore how authenticity has the potential to influence board dynamics and decision making and to enhance transparency and accountability.